2018
DOI: 10.1080/1028415x.2018.1500124
|View full text |Cite
|
Sign up to set email alerts
|

The green tea polyphenolic catechin epigallocatechin gallate and neuroprotection

Abstract: Epigallocatechin gallate is the most abundant composition of the tea catechins and is thought to be responsible for the majority of biological activity of green tea extracts such as antioxidant, anti-inflammatory, and antiapoptotic effects. Meanwhile, EGCG has been shown to be some of the neuroprotective effects against neural injuries and neurodegenerative diseases. This paper summarizes current knowledge on neuroprotective effects of EGCG and their molecular mechanisms responsible for the neuroprotection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 139 publications
1
34
0
Order By: Relevance
“…showed that PCs present in foods possess neuroprotective properties (Khalatbary & Khademi, 2020;Mohd Sairazi & Sirajudeen, 2020;Silva & Pogačnik, 2020;Zhao, Simon, & Wu, 2020). In conclusion, strong pieces of evidence are available to show that PCs in foods have significant neuroprotective properties.…”
Section: Neuroprotective Propertiesmentioning
confidence: 89%
“…showed that PCs present in foods possess neuroprotective properties (Khalatbary & Khademi, 2020;Mohd Sairazi & Sirajudeen, 2020;Silva & Pogačnik, 2020;Zhao, Simon, & Wu, 2020). In conclusion, strong pieces of evidence are available to show that PCs in foods have significant neuroprotective properties.…”
Section: Neuroprotective Propertiesmentioning
confidence: 89%
“…Tea leaves are steamed at a high temperature after harvesting to inactivate the polyphenol oxidizing enzymes, which protects the majority of vitamins present in the tea [4]. Thus, green tea possesses high levels of antioxidants and is used for its antiaging [58] and neuroprotective effects [58,59], alongside treating or preventing several diseases such as cancer [60], cardiovascular conditions [61,62], obesity [63], and so forth.…”
Section: Camellia Sinensis (Green Tea)mentioning
confidence: 99%
“…(−)-Epigallocatechin-3-gallate (EGCG) is the most abundant of the tea polyphenols, which display many beneficial properties, such as antioxidative, antiinflammatory, and antiapoptotic effects [ 14 , 15 ]. A neuroprotective effect has been found in Alzheimer’s disease, Parkinson’s disease, ischemic stroke, and spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%